Pembuatan sistem ozonizer untuk degradasi pewarna rhodamine B dengan metode peroxone menggunakan mikrokontroler ATMEGA 8535 - Rin Hafsahtul Asiah; Jatmiko Endro Suseno; Zaenul Muhlisin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2017)
The decrease of the quality water is caused by the dye waste of rhodamine B that found in liquid waste. One of the ways to treat that liquid waste is using the peroxone process that combines ozone (O3) and hydrogen peroxide (H2O2). The production of ozonizer system is vital due to its effectivity. The system is made by adding the microcontroller of Atmega 8535 as a timing controller that can adjust the duration of ozonizer system work. In addition, the concentration of H2O2 and the optimization of ozonation process were done to produce the most optimal degradation. The optimal ozone generator works on the frequency of 3500 Hz while the power is 2.15 Watt, 3576 V of voltage, and 0.6 mA of current with the average ozone production reaching 266 ppm every 30 minutes. The greater concentration of H2O2 that used and the longer ozonation time will increase the percentage degradation of rhodamine B. The greatest degradation percentage was achieved at the H2O2 concentration of 2500 ppm. The rhodamine B of 20 ppm was successfully degraded with the highest degradation percentage reaching 97% for 150 minutes.Keywords: Rhodamine B, Peroxone, Mikrokontroller